2017
DOI: 10.1136/bmjopen-2017-018993
|View full text |Cite
|
Sign up to set email alerts
|

A rapid review to identify physical activity accrued while playing golf

Abstract: ObjectiveTo identify physical activity (PA) accrued while playing golf and modifiers of PA accrued.DesignA rapid review of primary research studies. Quality was assessed using the National Heart, Lung, and Blood Institute quality assessment tool for cohort and cross-sectional studies.Methods and outcomesThe following databases were searched from 1900 to March 2017: SPORTDiscus, Web of Science, PsycINFO, MEDLINE, Google Scholar, Google Advanced Search, ProQuest, WHO International Clinical Trials Registry Platfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…8 Considering their work‐life situation, it seems they have more time to enjoy playing golf than younger players which can lead to higher round activity values during the playing season. Based on the results of this study, more than 90% of participants enjoyed the beneficial health effects of golf 10 , 11 , 12 , 14 , 29 by playing regularly at least once a week during the summer season. Previous researchers have demonstrated that using a nonelectronic (push or pull) cart during the round increases the intensity of playing compared with driving a golf buggy.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…8 Considering their work‐life situation, it seems they have more time to enjoy playing golf than younger players which can lead to higher round activity values during the playing season. Based on the results of this study, more than 90% of participants enjoyed the beneficial health effects of golf 10 , 11 , 12 , 14 , 29 by playing regularly at least once a week during the summer season. Previous researchers have demonstrated that using a nonelectronic (push or pull) cart during the round increases the intensity of playing compared with driving a golf buggy.…”
Section: Discussionmentioning
confidence: 87%
“…In contrast to the wider population, women golfers were more active than male golfers both in the summer ( p = 0.045) and in the winter seasons ( p = 0.017). With the best available evidence 11 highlighting that golf can provide moderate to vigorous aerobic activity, >95% of participants reported playing at least once per week and would exceed World Health Organization minimum recommendations. 80% of participants ( n = 223) achieved a high physical activity level in the summer season, and the majority (73%, n = 201) also in the winter season.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Golf is reported to be a moderate-intensity sport with a physical activity level of 4.8 METs, with an extended duration of 18 holes (a round) lasting anywhere from 4 to 5 h while covering distances over 10 km [ 1 , 2 , 3 , 4 , 5 , 6 ]. When played competitively, golf involves high cognitive loads, critical shot-making decisions, hand–eye coordination, high-level motor and biomechanical skills, and an extended duration of play that exceeds most other sports [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%